Aligned ZnO nanorod arrays growth on GaN QDs for excellent optoelectronic applications. (18th January 2016) - Sang, Dandan; Li, Hongdong; Wang, Qinglin
Abstract: Uniformly aligned ZnO nanorod (NR) arrays grown on GaN quantum dots (QDs) as preferred nucleation sites are imperative for designing field emission emitters, ultraviolet photodetectors and light-emitting diodes for a wide range of new optoelectronic applications. In a recent study (2015 Nanotechnology 26 415601 ), Qi et al reported a novel method of fabricating ZnO NRs arrays with uniform shape, the density of which is easily tunable by adjusting the density of GaN QDs. This approach opens a door to obtaining a combination of 0D and 1D structures for optoelectronic applications.